1996
DOI: 10.1097/00042560-199603010-00010
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HIV-1 DNA in Needle/Syringes, Paraphernalia, and Washes from Shooting Galleries in Miami: A Preliminary Laboratory Report

Abstract: Shared use of injection equipment (needle/syringes), registering, booting, and backloading are practices among injection drug users (IDUs) that increase the risk for transmission of human immunodeficiency virus type 1 (HIV-1). The sharing of injection paraphernalia (including cookers and cottons) and washwater for rinsing used needle/syringes and dissolving drugs could be potential sources for secondary transmission of HIV-1. Laboratory rinses were made from needle/syringes, cottons, and cookers obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 17 publications
1
34
0
1
Order By: Relevance
“…Finally, our definition of risk did not include the sharing of injection equipment other than needles or syringes. As HIV is detectable in cookers, cotton, and rinse water (Shah, Shapshak, Rivers, Stewart, & Weatherby, 1996), the sharing of such equipment may place IDUs at additional risk. We recommend further studies among Nepalese IDUs that include these measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our definition of risk did not include the sharing of injection equipment other than needles or syringes. As HIV is detectable in cookers, cotton, and rinse water (Shah, Shapshak, Rivers, Stewart, & Weatherby, 1996), the sharing of such equipment may place IDUs at additional risk. We recommend further studies among Nepalese IDUs that include these measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Using nested PCR, Shah et al 12 , detected viral particles of HIV-1 on a variety of objects visibly contaminated with blood, such as bits of cotton, spoons, lavatories, syringes, and needles collected at random from locales frequented by users of illicit injectable drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that it is possible to isolate the virus at up to four weeks after contamination of the needles. Using nested PCR, Shah et al 12 , were able to isolate viral particles of HIV-1 on various objects visibly contaminated with blood that were collected from locales frequented by drug users 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Epidemiologic links between HIV and sharing drug solution and equipment have been documented but are not as strong as the links between HIV and syringe sharing. 27,29,[33][34][35][36][37] The potential for HIV transmission through drug solution and equipment is inferred from studies that show association between these behaviors and other blood-borne viruses; findings of HIV antibodies and HIV polymerase chain reaction gene products in used syringes, cotton, cookers, and water 38 ; and laboratory studies demonstrating potential for HIV transmission.…”
Section: What Have We Learned About Individual Hiv Risk Behaviors Of mentioning
confidence: 99%